Polyaniline-bimetallic oxide composite material as well as preparation method and application thereof

By using polyaniline-bimetal oxide composite material, the problems of poor stability, selectivity and sensitivity of pure polyaniline material ammonia sensor are solved, and the ammonia sensing effect is achieved with high efficiency and good selectivity.

CN119861126APending Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311370381.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, ammonia sensors prepared by pure polyaniline materials have problems of poor stability, selectivity and low sensitivity.

Method used

Using polyaniline-bimetal oxide composite material, an ammonia sensor material with high specific surface area and fast response speed is prepared by mixing the bimetal oxide with aniline and polymerizing it.

Benefits of technology

It improves the ammonia sensing performance, enhances the selectivity and sensitivity of the material, and is simple in preparation and is easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119861126A_ABST
    Figure CN119861126A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas sensing, and discloses a polyaniline-bimetal oxide composite material and a preparation method and application thereof, the polyaniline-bimetal oxide composite material comprises a bimetal oxide and polyaniline loaded on the bimetal oxide, the specific surface area of the polyaniline-bimetallic oxide composite material is 100-500m < 2 > / g. The polyaniline-bimetallic oxide composite material is prepared through an in-situ polymerization method, the polyaniline-bimetallic oxide composite material has the specific surface area higher than that of a single component, more active sites are provided for adsorption of ammonia molecules, and the polyaniline-bimetallic oxide composite material has the advantages of being high in response speed, good in repeatability and selectivity and the like to ammonia at the room temperature; the sensing performance of the gas-sensitive material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to gas sensing technology, and in particular to a polyaniline-bimetallic oxide composite material and a preparation method and application thereof. Background Art

[0002] Ammonia (NH3) is an irritating, toxic, colorless, water-soluble, flammable gas. It is one of the main industrial raw materials for products used in agriculture, refrigeration technology, food, and medical facilities. Inhalation of NH3 by humans can cause acute respiratory diseases such as laryngitis and tracheobronchitis. In the workplace, the maximum permissible concentration of NH3 is 40ppm, while the detection limit of human smell is 25ppm. When the NH3 concentration exceeds 500ppm, it can cause lung damage and even death. Therefore, it is crucial to develop NH3 sensors with fast response speed and low detection limit and apply them to environmental analysis, chemical industry, and medical diagnosis.

[0003] At present, sensitive materials used as gas sensors can be divided into two categories: inorganic materials and organic materials. For inorganic sensitive materials such as SnO2, ZnO, Fe2O3, TiO2, they have the advantages of simple preparation methods and low raw material costs. However, the main limitations of this type of sensitive materials are their high operating temperature (usually 200-450°C) and poor selectivity. For organic sensitive materials such as polypyrrole, polyaniline (PANI), and metal phthalocyanine, they have the advantages of low operating temperature and simple preparation methods, but they have limitations such as long response time and recovery time and difficult processing. Therefore, the development of new functional ammonia sensing materials is still the direction of scientific researchers' efforts.

[0004] In order to improve the performance of sensing materials, researchers usually modify sensing materials by adopting strategies such as element doping and forming heterogeneous structures, such as compounding organic materials with inorganic materials to make up for the shortcomings of each other in performance. PANI, as a commonly used organic conductive polymer, is widely used in the preparation of gas sensors due to its easy synthesis, good environmental stability, high sensitivity, fast response speed, low cost, reversible redox reaction, and operation at room temperature. In the past few decades, the combination of conductive polymers and inorganic materials to form composite materials is an effective way to improve the mechanical strength and sensing properties of gas sensing materials. There are endless reports on adding a variety of inorganic nanofillers to polyaniline for gas detection, such as PANI / In2O3 for H2, NO2, CO gas detection, PANI / TiO2 for NH3, CO gas detection, multi-walled carbon nanotubes / PANI or graphene / PANI for H2 detection, functionalized single-walled carbon nanotubes / PANI for NH3, NO2, H2S gas detection, WO3 hollow spheres / PANI for NH3 gas detection, etc. However, single metal oxides such as In2O3, TiO2, WO3 and carbon materials such as multi-walled carbon nanotubes, single-walled carbon nanotubes, and graphene have poor energy storage and sensing performance, poor reproducibility and sensitivity, and the detection limit cannot meet the needs of production and life. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of poor stability, low selectivity and low sensitivity of ammonia sensors prepared from pure PANI materials in the prior art, and to provide a polyaniline-bimetallic oxide composite material and a preparation method and application thereof. The polyaniline-bimetallic oxide composite material can improve the sensing performance, and the preparation process is simple to operate, easy to industrialize, and is conducive to the large-scale production and application promotion of sensors.

[0006] In order to achieve the above object, the present invention provides a polyaniline-bimetallic oxide composite material, wherein the polyaniline-bimetallic oxide composite material comprises a bimetallic oxide and polyaniline supported on the bimetallic oxide; the specific surface area of ​​the polyaniline-bimetallic oxide composite material is 100-500m 2 / g.

[0007] Preferably, the content of the polyaniline is 200-800 parts by weight relative to 100 parts by weight of the bimetallic oxide.

[0008] Preferably, the specific surface area of ​​the polyaniline-bimetallic oxide composite material is 150-250 m 2 / g.

[0009] Preferably, the bimetallic oxide is selected from one or more of CoMoO4, NiCo2O4, ZnCo2O4 or CuCo2O4.

[0010] The second aspect of the present invention provides a method for preparing the above-mentioned polyaniline-bimetallic oxide composite material, the preparation method comprising the following steps:

[0011] (1) mixing a bimetallic oxide with aniline to obtain an aniline / bimetallic oxide dispersion;

[0012] (2) mixing the aniline / bimetallic oxide dispersion obtained in step (1) with an initiator to carry out a polymerization reaction.

[0013] Preferably, the specific steps of step (1) include:

[0014] (a) mixing a bimetallic oxide with water to obtain a bimetallic oxide solution;

[0015] (b) mixing aniline with a solvent to obtain an aniline solution;

[0016] (c) mixing the bimetallic oxide solution obtained in step (a) with the aniline solution obtained in step (b), and then performing ultrasound to obtain an aniline / bimetallic oxide mixture;

[0017] (d) stirring the aniline / bimetallic oxide mixture obtained in step (c) to obtain an aniline / bimetallic oxide dispersion.

[0018] Preferably, in step (c), the ultrasonic conditions include: time of 0.5-2h, temperature of 10-40°C, and power of 100-1000W.

[0019] Preferably, in step (d), the stirring conditions include: temperature of -1 to 1°C and time of 1 to 3 hours.

[0020] Preferably, the solid-to-liquid ratio of the bimetallic oxide and the aniline is 1 g: (2-8) mL.

[0021] Preferably, the weight ratio of the bimetallic oxide to the initiator is 1:(5-20).

[0022] Preferably, in step (2), the initiator is selected from one or more of ammonium persulfate, ferric chloride, ferric tetrachloride or aluminum chloride.

[0023] Preferably, in step (2), the polymerization reaction is an in-situ polymerization reaction.

[0024] Preferably, in step (2), the conditions of the in-situ polymerization reaction include: time of 5-12 hours and temperature of 0-40°C.

[0025] The third aspect of the present invention provides the use of the polyaniline-bimetallic oxide composite material in ammonia detection.

[0026] A fourth aspect of the present invention provides use of the polyaniline-bimetallic oxide composite material in preparing an ammonia gas sensor.

[0027] A fifth aspect of the present invention provides an ammonia gas sensor, wherein the ammonia gas sensor comprises the above-mentioned polyaniline-bimetallic oxide composite material.

[0028] Compared with the prior art, the above technical solution of the present invention has the following advantages:

[0029] 1. The present invention prepares a polyaniline-bimetallic oxide composite material by an in-situ polymerization method. The polyaniline-bimetallic oxide composite material has a higher specific surface area than a single component, which provides more active sites for the adsorption of ammonia molecules. It has the characteristics of fast response speed, good repeatability and selectivity to ammonia at room temperature, and can improve the sensing performance of gas-sensitive materials. In addition, the ammonia response performance of the polyaniline-bimetallic oxide composite material is significantly better than that of the original polyaniline, indicating that the addition of bimetallic oxide plays a key role in improving the sensing performance of polyaniline.

[0030] 2. The present invention uses bimetallic oxides as modifiers to improve the sensing performance of polyaniline. The prepared polyaniline-bimetallic oxide composite material has a series of unique physical and chemical properties. The bimetallic oxides can synergistically accelerate the response speed of ammonia and the deprotonation / protonation process of the original polyaniline.

[0031] 3. In the polyaniline-bimetallic oxide composite material prepared by the present invention, polyaniline is loaded on the bimetallic oxide to form a structure similar to a coaxial cable, which can accelerate the unidirectional transmission of electrical signals, thereby greatly improving the response ability of the polyaniline-bimetallic oxide composite material.

[0032] 4. The present invention adopts an in-situ self-assembly method to modify polyaniline on a bimetallic oxide, and develops a new type of PP homotype heterojunction sensor. The obtained polyaniline-bimetallic oxide composite material can be used to prepare an ammonia gas sensor, which can be used for the detection of ammonia (NH3) at room temperature.

[0033] 5. In the present invention, due to the synergistic oxidation of the bimetallic oxide and the initiator, the introduction of the bimetallic oxide improves the protonation process of PANI, and the enhanced PANI protonation provides more =NH for the adsorption of NH3 molecules. + groups, thereby enhancing the NH3 sensing performance of the sensor.

[0034] 6. The process of preparing the polyaniline-bimetallic oxide composite material of the present invention is simple to operate and easy to industrialize, which is conducive to the large-scale production and application promotion of sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a SEM scanning electron microscope image of CoMoO4 in Example 1 of the present invention;

[0036] Figure 2 is a SEM scanning electron microscope image of the PANI-CoMoO4 composite material in Example 1 of the present invention;

[0037] Figure 3 is a TEM transmission electron microscope image of the PANI-CoMoO4 composite material in Example 1 of the present invention;

[0038] Figure 4 is the XRD curve diagram of the PANI-CoMoO4 composite material, PANI and CoMoO4 in Example 1 of the present invention;

[0039] Figure 5 This is a test diagram of the specific surface area of ​​the PANI-CoMoO4 composite material prepared in Example 1 of the present invention;

[0040] Figure 6 The ammonia gas sensor containing the PANI-CoMoO4 composite material prepared in Example 1 of the present invention and the ammonia gas sensor containing only PANI prepared in Comparative Example 1 are placed in ammonia of different concentrations, and the response intensity and response time of the ammonia gas sensor;

[0041] Figure 7 is the ratio of the response intensity of the ammonia gas sensor containing the PANI-CoMoO4 composite material prepared in Example 1 of the present invention to hydrogen sulfide, methane, carbon monoxide and nitric oxide to the response intensity to ammonia;

[0042] Figure 8 This is a test chart of the repeatability and stability of the ammonia gas sensor prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] The first aspect of the present invention provides a polyaniline-bimetallic oxide composite material, wherein the polyaniline-bimetallic oxide composite material comprises a bimetallic oxide and polyaniline supported on the bimetallic oxide; the specific surface area of ​​the polyaniline-bimetallic oxide composite material is 100-500m 2 / g, preferably 150-250m 2 / g, specifically, the specific surface area of ​​the polyaniline-bimetallic oxide composite material can be 150m 2 / g, 170m 2 / g, 200m 2 / g, 220m 2 / g or 250m 2 / g.

[0046] In the polyaniline-bimetallic oxide composite material described in the present invention, the content of the polyaniline is 200-800 parts by weight relative to 100 parts by weight of the bimetallic oxide. Specifically, the content of the polyaniline can be 200 parts by weight, 300 parts by weight, 400 parts by weight, 500 parts by weight, 600 parts by weight, 700 parts by weight or 800 parts by weight relative to 100 parts by weight of the bimetallic oxide.

[0047] In the polyaniline-bimetallic oxide composite material of the present invention, the contents of bimetallic oxide and polyaniline can be calculated based on the amounts of raw materials used in the preparation process.

[0048] In the polyaniline-bimetallic oxide composite material described in the present invention, since the bimetallic oxide not only has the advantages of a single metal oxide, but also has the advantages of rich multivalent cations, unique crystal structure characteristics, controllable components, etc., it becomes a potential energy storage and sensor material, and polyaniline is loaded on the bimetallic oxide to form a structure similar to a coaxial cable, which can accelerate the unidirectional transmission of electrical signals, thereby greatly improving the responsiveness of the polyaniline-bimetallic oxide composite material.

[0049] In a preferred embodiment of the present invention, the bimetallic oxide is in a rod shape, and the diameter of the bimetallic oxide is 0.5-200 μm, and the length is 5-30 μm; in a further preferred embodiment of the present invention, the diameter of the bimetallic oxide is 1-5 μm, and the length is 10-20 mm. Specifically, the diameter of the bimetallic oxide can be 1 μm, 2 μm, 3 μm, 4 μm or 5 μm, and the length of the bimetallic oxide can be 10 mm, 12 mm, 14 mm, 16 mm, 18 mm or 20 mm.

[0050] In the present invention, the bimetallic oxide is selected from one or more of CoMoO4, NiCo2O4, ZnCo2O4 or CuCo2O4, preferably CoMoO4.

[0051] In the present invention, since cobalt molybdenum oxide (CoMoO4) is a typical bimetallic oxide and exhibits high catalytic activity and stability in catalysis, batteries, and supercapacitors, in order to make the polyaniline-bimetallic oxide composite material have better performance, the bimetallic oxide is preferably CoMoO4.

[0052] The second aspect of the present invention provides a method for preparing the above-mentioned polyaniline-bimetallic oxide composite material, the preparation method comprising the following steps:

[0053] (1) mixing a bimetallic oxide with aniline to obtain an aniline / bimetallic oxide dispersion;

[0054] (2) mixing the aniline / bimetallic oxide dispersion obtained in step (1) with an initiator to carry out a polymerization reaction.

[0055] In the preparation method of the present invention, in step (1), the bimetallic oxide can be commercially available or homemade. When the bimetallic oxide is homemade, the preparation method of the bimetallic oxide comprises:

[0056] (I) mixing nitrate and molybdate to obtain a metal salt mixed solution;

[0057] (II) subjecting the metal salt mixed solution to a hydrothermal reaction and then drying.

[0058] In the preparation method of the bimetallic oxide described in the present invention, in step (I), the nitrate is selected from copper nitrate, nickel nitrate, zinc nitrate or cobalt nitrate, the molybdate is selected from sodium molybdate or potassium molybdate, and the molar ratio of the nitrate to the molybdate is 1:(0.8-1.2).

[0059] In a specific embodiment of the present invention, the nitrate is cobalt nitrate hexahydrate (Co(NO3)2·6H2O), and the molybdate is sodium molybdate dihydrate (Na2MoO4·2H2O).

[0060] In the method for preparing the bimetallic oxide of the present invention, the specific steps of mixing the nitrate and the molybdate in step (I) include:

[0061] S1. mixing nitrate with water to obtain a nitrate solution;

[0062] S2, mixing molybdate with water to obtain a molybdate solution;

[0063] S3. Mix the nitrate solution and the molybdate solution and stir.

[0064] In the preparation method of the bimetallic oxide described in the present invention, in step S1, there is no special requirement for the amount of nitrate and water used, as long as the nitrate can be completely dissolved. In a preferred case, the molar volume ratio of the nitrate to water is 1 mmol: (8-12) mL.

[0065] In the preparation method of the bimetallic oxide described in the present invention, in step S2, there is no special requirement for the amount of molybdate and water used, as long as the molybdate can be completely dissolved. In a preferred case, the molar volume ratio of the molybdate to water is 1 mmol: (8-12) mL.

[0066] In the preparation method of the bimetallic oxide described in the present invention, in step S3, in order to make the nitrate solution and the molybdate solution mix evenly, the stirring time needs to be controlled to 8-12 minutes. Specifically, the stirring time can be 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes.

[0067] In the preparation method of the bimetallic oxide described in the present invention, in order to prepare the bimetallic oxide with more suitable morphology and size, it is necessary to control the conditions of the hydrothermal reaction within a suitable range. Preferably, in step (II), the conditions of the hydrothermal reaction include: temperature of 130-160°C and time of 8-24h.

[0068] In a specific embodiment, the temperature of the hydrothermal reaction can be 130°C, 135°C, 140°C, 145°C, 150°C, 155°C or 160°C, and the time of the hydrothermal reaction can be 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.

[0069] In the preparation method of the bimetallic oxide described in the present invention, there is no special requirement for the equipment used for the hydrothermal reaction, and it can be a conventional choice in the art. In a specific embodiment, the hydrothermal reaction is carried out in a high-pressure reactor.

[0070] In a preferred embodiment, after the hydrothermal reaction in step (II) is completed, a bimetallic oxide solution is obtained, and then the obtained bimetallic oxide solution needs to be subjected to solid-liquid separation to obtain a bimetallic oxide solid, and then the obtained bimetallic oxide solid is washed 3-6 times to remove the unreacted raw materials and then dried.

[0071] In the preparation method of the bimetallic oxide described in the present invention, in step (II), the drying conditions include: temperature of 70-90° C. and time of 8-12 h.

[0072] In the preparation method of the polyaniline-bimetallic oxide composite material of the present invention, in order to make the bimetallic oxide and aniline mix more uniformly, in a preferred case, the specific steps of step (1) include:

[0073] (a) mixing a bimetallic oxide with water to obtain a bimetallic oxide solution;

[0074] (b) mixing aniline with a solvent to obtain an aniline solution;

[0075] (c) mixing the bimetallic oxide solution obtained in step (a) with the aniline solution obtained in step (b), and then performing ultrasound to obtain an aniline / bimetallic oxide mixture;

[0076] (d) stirring the aniline / bimetallic oxide mixture obtained in step (c) to obtain an aniline / bimetallic oxide dispersion.

[0077] In step (a) of the present invention, there is no special requirement for the amount of the bimetallic oxide and water, as long as the bimetallic oxide can be completely dissolved. In a preferred case, the solid-liquid ratio of the bimetallic oxide to water is 1 g: (40-120) mL.

[0078] In step (b) of the present invention, there is no special requirement for the amount of aniline and the solvent, and the aniline can be completely dissolved. In a preferred case, the volume ratio of the amount of aniline to the amount of the solvent is 1:(10-30).

[0079] In a preferred embodiment, in step (b), there is no special requirement for the selection of the solvent, as long as it can dissolve aniline. In a preferred case, the solvent is selected from hydrochloric acid solution, chloroform or methanol, preferably hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 0.5-3 mol / L. Specifically, the concentration of the hydrochloric acid solution can be 0.5 mol / L, 1 mol / L, 2 mol / L or 3 mol / L.

[0080] In a specific implementation manner of step (b), the concentration of the hydrochloric acid solution is 1 mol / L.

[0081] In step (c) of the present invention, in order to make the materials mixed more uniformly, after the bimetallic oxide solution obtained in step (a) and the aniline solution obtained in step (b) are mixed, ultrasound is required to obtain a uniformly mixed aniline / bimetallic oxide mixture.

[0082] In the preferred case of step (c), the ultrasonic conditions include: time of 0.5-2h, temperature of 10-40°C, power of 100-1000W, preferably 500-900W.

[0083] In the preparation method of the polyaniline-bimetallic oxide composite material described in the present invention, in step (d), in order to obtain a uniformly mixed aniline / bimetallic oxide dispersion and thereby enable the polyaniline to be uniformly loaded on the bimetallic oxide, it is necessary to control the stirring conditions. Therefore, in a preferred case, the stirring conditions include: a temperature of -1 to 1°C and a time of 1 to 3 hours.

[0084] In a specific embodiment of step (d), the stirring temperature is 0°C.

[0085] In a preferred embodiment, in order to obtain a polyaniline-bimetallic oxide composite material with better performance, it is necessary to further control the amount of bimetallic oxide, aniline and initiator, the solid-liquid ratio of the bimetallic oxide and the aniline is 1g:(2-8)mL, and the weight ratio of the bimetallic oxide and the initiator is 1:(5-20). Specifically, the solid-liquid ratio of the bimetallic oxide and the aniline can be 1g:2mL, 1g:4mL, 1g:6mL or 1g:8mL, and the weight ratio of the bimetallic oxide and the initiator can be 1:5, 1:10, 1:15 or 1:20.

[0086] In a preferred case, in order to evenly mix the bimetallic oxide, aniline and initiator and fully carry out the polymerization reaction, it is necessary to first mix the initiator with the solvent in step (2) to obtain an initiator solution, and then mix the initiator solution with the aniline / bimetallic oxide dispersion to carry out the polymerization reaction.

[0087] In the preparation method of the polyaniline-bimetallic oxide composite material of the present invention, there is no special requirement for the amount of the initiator and the solvent, and the initiator can be completely dissolved. In a preferred case, the solid-liquid ratio of the initiator to the solvent is 1g:(5-25)mL. Specifically, the solid-liquid ratio of the initiator to the solvent can be 1g:5mL, 1g:10mL, 1g:15mL, 1g:20mL or 1g:25mL.

[0088] In a preferred case, in order to fully dissolve the initiator, the solvent is selected from hydrochloric acid solution, chloroform or methanol, preferably hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 0.5-3 mol / L. Specifically, the concentration of the hydrochloric acid solution can be 0.5 mol / L, 1 mol / L, 2 mol / L or 3 mol / L.

[0089] In a specific implementation manner of step (2) of the present invention, the concentration of the hydrochloric acid solution is 1 mol / L.

[0090] In a preferred embodiment, in order to evenly mix the initiator solution with the aniline / bimetallic oxide dispersion, the initiator solution is added dropwise to the aniline / bimetallic oxide dispersion. There is no special requirement for the dropping speed of the initiator solution, and even mixing is sufficient.

[0091] In the method for preparing the polyaniline-bimetallic oxide composite material of the present invention, in step (2), there is no special requirement for the initiator, as long as it can initiate the polymerization reaction, and it can be a conventional choice in the art. In a preferred embodiment, the initiator is selected from one or more of ammonium persulfate, ferric chloride, ferric tetrachloride or aluminum chloride, and is more preferably ammonium persulfate.

[0092] In the method for preparing the polyaniline-bimetallic oxide composite material of the present invention, in order to control the uniform loading of polyaniline on the surface of the bimetallic oxide in step (2), the polymerization reaction is an in-situ polymerization reaction. Preferably, the conditions of the in-situ polymerization reaction include: time for 3-15h and temperature for 0-55°C; further preferably, the conditions of the in-situ polymerization reaction include: time for 5-12h and temperature for 0-40°C.

[0093] In a specific embodiment, the time of the in situ polymerization reaction can be 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, and the temperature of the in situ polymerization reaction can be 0°C, 5°C, 15°C, 20°C, 25°C, 30°C, 35°C or 40°C.

[0094] In the method for preparing the polyaniline-bimetallic oxide composite material of the present invention, after the polymerization reaction in step (2) is completed, the obtained material needs to be separated into solid and liquid, the obtained solid material is washed 3-5 times, the unreacted raw materials are removed, and then dried to obtain the polyaniline-bimetallic oxide composite material.

[0095] In a preferred embodiment, the drying conditions include: a temperature of 50-70°C and a time of 8-24h. Specifically, the drying temperature can be 50°C, 55°C, 60°C, 65°C or 70°C, and the drying time can be 8h, 10h, 15h, 20h or 24h.

[0096] The third aspect of the present invention provides the use of the polyaniline-bimetallic oxide composite material in ammonia detection.

[0097] A fourth aspect of the present invention provides use of the polyaniline-bimetallic oxide composite material in preparing an ammonia gas sensor.

[0098] A fifth aspect of the present invention provides an ammonia gas sensor, wherein the ammonia gas sensor comprises the above-mentioned polyaniline-bimetallic oxide composite material.

[0099] The present invention will be described in detail below through examples, comparative examples and test examples. The examples, comparative examples and test examples are implemented on the premise of the technical solution of the present invention, and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.

[0100] The experimental methods in the following embodiments, comparative examples and test examples, unless otherwise specified, are conventional methods in the art. The experimental materials used in the following embodiments, comparative examples and test examples, unless otherwise specified, are all commercially available.

[0101] In the following examples and comparative examples, the sources of the reagent raw materials used are as follows:

[0102] Co(NO3)2·6H2O and Na2MoO4·2H2O were purchased from Aladdin; hydrochloric acid and aniline were purchased from Inotech; NiCo2O4, ZnCo2O4, CuCo2O4, ammonium persulfate, pineneol, and Al2O3 were purchased from Sinopharm Group.

[0103] Example 1

[0104] (1) Dissolve 0.5mmol Co(NO3)2·6H2O in 5mL of deionized water to obtain Co(NO3)2·6H2O solution; Dissolve 0.5mmol Na2MoO4·2H2O in 5mL of deionized water to obtain Na2MoO4·2H2O solution; Then mix the Co(NO3)2·6H2O solution with the Na2MoO4·2H2O solution and stir for 10min to obtain a mixed solution; Then transfer the mixed solution to an 80mL autoclave and perform a hydrothermal reaction at 150°C for 24h; After the hydrothermal reaction is completed, centrifuge the obtained product in a centrifuge, and after the centrifugation is completed, pour out the supernatant to leave the solid, and wash the solid 5 times with deionized water; Then dry the washed solid in an oven at 80°C for 8h to obtain CoMoO4;

[0105] (2) taking 0.1 g of the above CoMoO4 and dispersing it in 10 mL of deionized water to obtain a CoMoO4 solution, dissolving 700 μL of aniline in 10 mL of a 1 mol / L hydrochloric acid solution to obtain an aniline solution, and then adding the aniline solution to the CoMoO4 solution to obtain an aniline / CoMoO4 mixture (the solid-to-liquid ratio of CoMoO4 to aniline is 1 g:7 mL); placing the aniline / CoMoO4 mixture in a 100 mL beaker and ultrasonically treating it for 0.5 h (ultrasonic temperature is 25° C., ultrasonic power is 800 W), and then stirring it in an ice-water bath at 0° C. for 2 h to obtain an aniline / CoMoO4 dispersion;

[0106] (3) 1.5 g of ammonium persulfate was dissolved in 10 mL of 1 mol / L hydrochloric acid solution to obtain an ammonium persulfate solution, and then the ammonium persulfate solution was added dropwise to the aniline / CoMoO4 dispersion, and an in-situ polymerization reaction was carried out under stirring. The in-situ polymerization reaction time was 5 h and the temperature was 0° C. After the in-situ polymerization reaction was completed, the obtained product was filtered to obtain a solid material; then the solid material was washed with deionized water for 3 times, and then the solid material was dried in an oven at 60° C. for 8 h to obtain a PANI-CoMoO4 composite material A1;

[0107] (4) 3 mg of PANI-CoMoO4 composite material A1 was dispersed in 1 mL of pine alcohol and ground into a paste. The paste was applied to the surface of an Al2O3 tube with a length of 4 mm and an inner diameter of 0.8 mm using a brush. The surface of the Al2O3 tube had two gold electrodes with a distance of 1 mm between the two gold electrodes. Two platinum wires were connected to each gold electrode respectively. After the Ni / Cr wire passed through the Al2O3 tube, it was welded to the sensor base together with the platinum wire to obtain an ammonia gas sensitive sensor B1.

[0108] Example 2

[0109] (1) Dissolve 0.5mmol Co(NO3)2·6H2O in 5mL of deionized water to obtain Co(NO3)2·6H2O solution; Dissolve 0.5mmol Na2MoO4·2H2O in 5mL of deionized water to obtain Na2MoO4·2H2O solution; Then mix the Co(NO3)2·6H2O solution with the Na2MoO4·2H2O solution and stir for 10min to obtain a mixed solution; Then transfer the mixed solution to an 80mL autoclave and perform a hydrothermal reaction at 130°C for 8h; After the hydrothermal reaction is completed, centrifuge the obtained product in a centrifuge, and after the centrifugation is completed, pour out the supernatant to leave the solid, and wash the solid 5 times with deionized water; Then dry the washed solid in an oven at 80°C for 12h to obtain CoMoO4;

[0110] (2) 0.1 g of the above CoMoO4 was dispersed in 10 mL of deionized water to obtain a CoMoO4 solution, 600 μL of aniline was dissolved in 20 mL of a 1 mol / L hydrochloric acid solution to obtain an aniline solution, and then the aniline solution was added to the CoMoO4 solution to obtain an aniline / CoMoO4 mixture (the solid-to-liquid ratio of CoMoO4 to aniline was 1 g:6 mL); the aniline / CoMoO4 mixture was placed in a 100 mL beaker and ultrasonically treated for 0.5 h (ultrasonic temperature was 25° C., ultrasonic power was 800 W), and then stirred in an ice-water bath at 0° C. for 2 h to obtain an aniline / CoMoO4 dispersion;

[0111] (3) 1.5 g of ammonium persulfate was dissolved in 30 mL of 1 mol / L hydrochloric acid solution to obtain an ammonium persulfate solution, and then the ammonium persulfate solution was added dropwise to the aniline / CoMoO4 dispersion, and an in-situ polymerization reaction was carried out under stirring. The in-situ polymerization reaction time was 8 h and the temperature was 20° C. After the in-situ polymerization reaction was completed, the obtained product was filtered to obtain a solid material; then the solid material was washed with deionized water 3 times, and then the solid material was dried in an oven at 60° C. for 8 h to obtain a PANI-CoMoO4 composite material A2;

[0112] (4) 4 mg of PANI-CoMoO4 composite material A2 was dispersed in 1.2 mL of pine alcohol and ground into a paste. The paste was applied to the surface of an Al2O3 tube with a length of 4 mm and an inner diameter of 0.8 mm using a brush. The surface of the Al2O3 tube had two gold electrodes with a distance of 1 mm between the two gold electrodes. Two platinum wires were connected to each gold electrode respectively. After the Ni / Cr wire passed through the Al2O3 tube, it was welded to the sensor base together with the platinum wire to obtain an ammonia gas sensitive sensor B2.

[0113] Example 3

[0114] (1) Dissolve 0.5mmol Co(NO3)2·6H2O in 5mL of deionized water to obtain Co(NO3)2·6H2O solution; dissolve 0.5mmol Na2MoO4·2H2O in 10mL of deionized water to obtain Na2MoO4·2H2O solution; then mix the Co(NO3)2·6H2O solution and the Na2MoO4·2H2O solution and stir for 10min to obtain a mixed solution; then transfer the mixed solution to an 80mL autoclave and perform a hydrothermal reaction at 160°C for 8h; after the hydrothermal reaction is completed, centrifuge the obtained product in a centrifuge, and after the centrifugation is completed, pour out the supernatant to leave the solid, and wash the solid 5 times with deionized water; then dry the washed solid in an oven at 80°C for 12h to obtain CoMoO4;

[0115] (2) 0.1 g of the above CoMoO4 was dispersed in 10 mL of deionized water to obtain a CoMoO4 solution, 500 μL of aniline was dissolved in 20 mL of a 1 mol / L hydrochloric acid solution to obtain an aniline solution, and then the aniline solution was added to the CoMoO4 solution to obtain an aniline / CoMoO4 mixture (the solid-to-liquid ratio of CoMoO4 to aniline was 1 g:5 mL); the aniline / CoMoO4 mixture was placed in a 100 mL beaker and ultrasonically treated for 0.5 h (ultrasonic temperature was 25° C., ultrasonic power was 800 W), and then stirred in an ice-water bath at 0° C. for 3 h to obtain an aniline / CoMoO4 dispersion;

[0116] (3) 1.5 g of ammonium persulfate was dissolved in 30 mL of 1 mol / L hydrochloric acid solution to obtain an ammonium persulfate solution, and then the ammonium persulfate solution was added dropwise to the aniline / CoMoO4 dispersion, and an in-situ polymerization reaction was carried out under stirring. The in-situ polymerization reaction time was 10 h and the temperature was 20° C. After the in-situ polymerization reaction was completed, the obtained product was filtered to obtain a solid material; then the solid material was washed with deionized water for 3 times, and then the solid material was dried in an oven at 60° C. for 8 h to obtain a PANI-CoMoO4 composite material A3;

[0117] (4) 5 mg of PANI-CoMoO4 composite material A3 was dispersed in 1.5 mL of pine alcohol and ground into a paste. The paste was applied to the surface of an Al2O3 tube with a length of 4 mm and an inner diameter of 0.8 mm using a brush. The surface of the Al2O3 tube had two gold electrodes with a distance of 1 mm between the two gold electrodes. Two platinum wires were connected to each gold electrode respectively. After the Ni / Cr wire passed through the Al2O3 tube, it was welded to the sensor base together with the platinum wire to obtain an ammonia gas sensitive sensor B3.

[0118] Example 4

[0119] (1) Dissolve 0.5mmol Co(NO3)2·6H2O in 5mL of deionized water to obtain Co(NO3)2·6H2O solution; dissolve 0.5mmol Na2MoO4·2H2O in 10mL of deionized water to obtain Na2MoO4·2H2O solution; then mix the Co(NO3)2·6H2O solution and the Na2MoO4·2H2O solution and stir for 10min to obtain a mixed solution; then transfer the mixed solution to an 80mL autoclave and perform a hydrothermal reaction at 160°C for 8h; after the hydrothermal reaction is completed, centrifuge the obtained product in a centrifuge, and after the centrifugation is completed, pour out the supernatant to leave the solid, and wash the solid 5 times with deionized water; then dry the washed solid in an oven at 80°C for 12h to obtain CoMoO4;

[0120] (2) 0.1 g of the above CoMoO4 was dispersed in 10 mL of deionized water to obtain a CoMoO4 solution, 200 μL of aniline was dissolved in 20 mL of 1 mol / L hydrochloric acid solution to obtain an aniline solution, and then the aniline solution was added to the CoMoO4 solution to obtain an aniline / CoMoO4 mixture (the solid-to-liquid ratio of CoMoO4 to aniline was 1 g:2 mL); the aniline / CoMoO4 mixture was placed in a 100 mL beaker and ultrasonically treated for 0.5 h (ultrasonic temperature was 25° C., ultrasonic power was 800 W), and then stirred in an ice-water bath at 0° C. for 4 h to obtain an aniline / CoMoO4 dispersion;

[0121] (3) 1.5 g of ammonium persulfate was dissolved in 30 mL of 1 mol / L hydrochloric acid solution to obtain an ammonium persulfate solution, and then the ammonium persulfate solution was added dropwise to the aniline / CoMoO4 dispersion, and an in-situ polymerization reaction was carried out under stirring. The in-situ polymerization reaction time was 11 h and the temperature was 20° C. After the in-situ polymerization reaction was completed, the obtained product was filtered to obtain a solid material; then the solid was washed with deionized water 3 times, and then the solid material was dried in an oven at 60° C. for 8 h to obtain a PANI-CoMoO4 composite material A4;

[0122] (4) 5 mg of PANI-CoMoO4 composite material A4 was dispersed in 1.5 mL of pine alcohol and ground into a paste. The paste was applied to the surface of an Al2O3 tube with a length of 4 mm and an inner diameter of 0.8 mm using a brush. The surface of the Al2O3 tube had two gold electrodes with a distance of 1 mm between the two gold electrodes. Two platinum wires were connected to each gold electrode respectively. After the Ni / Cr wire passed through the Al2O3 tube, it was welded to the sensor base together with the platinum wire to obtain an ammonia gas sensitive sensor B4.

[0123] Example 5

[0124] (1) Dissolve 0.5mmol Co(NO3)2·6H2O in 5mL of deionized water to obtain Co(NO3)2·6H2O solution; dissolve 0.5mmol Na2MoO4·2H2O in 10mL of deionized water to obtain Na2MoO4·2H2O solution; then mix the Co(NO3)2·6H2O solution and the Na2MoO4·2H2O solution and stir for 10min to obtain a mixed solution; then transfer the mixed solution to an 80mL autoclave and perform a hydrothermal reaction at 160°C for 8h; after the hydrothermal reaction is completed, centrifuge the obtained product in a centrifuge, and after the centrifugation is completed, pour out the supernatant to leave the solid, and wash the solid 5 times with deionized water; then dry the washed solid in an oven at 80°C for 12h to obtain CoMoO4;

[0125] (2) 0.1 g of the above CoMoO4 was dispersed in 10 mL of deionized water to obtain a CoMoO4 solution, 800 μL of aniline was dissolved in 20 mL of a 1 mol / L hydrochloric acid solution to obtain an aniline solution, and then the aniline solution was added to the CoMoO4 solution to obtain an aniline / CoMoO4 mixture (the solid-to-liquid ratio of CoMoO4 to aniline was 1 g:8 mL); the aniline / CoMoO4 mixture was placed in a 100 mL beaker and ultrasonically treated for 0.5 h (ultrasonic temperature was 25° C., ultrasonic power was 800 W), and then stirred in an ice-water bath at 0° C. for 2 h to obtain an aniline / CoMoO4 dispersion;

[0126] (3) 1.5 g of ammonium persulfate was dissolved in 30 mL of 1 mol / L hydrochloric acid solution to obtain an ammonium persulfate solution, and then the ammonium persulfate solution was added dropwise to the aniline / CoMoO4 dispersion, and an in-situ polymerization reaction was carried out under stirring. The in-situ polymerization reaction time was 12 h and the temperature was 40° C. After the in-situ polymerization reaction was completed, the obtained product was filtered to obtain a solid material; then the solid material was washed with deionized water for 3 times, and then the solid material was dried in an oven at 60° C. for 8 h to obtain a PANI-CoMoO4 composite material A5;

[0127] (4) 5 mg of PANI-CoMoO4 composite material A5 was dispersed in 1.5 mL of pine alcohol and ground into a paste. The paste was applied to the surface of an Al2O3 tube with a length of 4 mm and an inner diameter of 0.8 mm using a brush. The surface of the Al2O3 tube had two gold electrodes with a distance of 1 mm between the two gold electrodes. Two platinum wires were connected to each gold electrode respectively. After the Ni / Cr wire passed through the Al2O3 tube, it was welded to the sensor base together with the platinum wire to obtain an ammonia gas sensitive sensor B5.

[0128] Example 6

[0129] The method of Example 1 was followed, except that CoMoO4 was replaced by NiCo2O4, to obtain a PANI-NiCo2O4 composite material A6, and further to obtain an ammonia gas sensitive sensor B6.

[0130] Example 7

[0131] The method of Example 1 was followed, except that CoMoO4 was replaced by ZnCo2O4, to obtain a PANI-ZnCo2O4 composite material A7, and further to obtain an ammonia gas sensitive sensor B7.

[0132] Example 8

[0133] The method of Example 1 was followed, except that CoMoO4 was replaced by CuCo2O4, to obtain a PANI-CuCo2O4 composite material A8, and further to obtain an ammonia gas sensitive sensor B8.

[0134] Example 9

[0135] According to the method of Example 1, except that the amount of aniline used was 150 μL, and the solid-liquid ratio of CoMoO4 to aniline was 1 g:1.5 mL, a PANI-CoMoO4 composite material A9 was obtained, and further an ammonia gas sensitive sensor B9 was obtained.

[0136] Example 10

[0137] According to the method of Example 1, except that the amount of aniline used was 900 μL, and the solid-liquid ratio of CoMoO4 to aniline was 1 g:9 mL, a PANI-CoMoO4 composite material A10 was prepared, and an ammonia gas sensitive sensor B10 was further obtained.

[0138] Comparative Example 1

[0139] (1) 700 μL of aniline was dissolved in 10 mL of 1 mol / L hydrochloric acid solution to obtain an aniline solution, the aniline solution was placed in a 100 mL beaker and ultrasonicated for 0.5 h (ultrasonic temperature was 25° C., ultrasonic power was 800 W), and then stirred in an ice water bath at 0° C. for 2 h; 1.5 g of ammonium persulfate was dissolved in 10 mL of 1 mol / L hydrochloric acid solution to obtain an ammonium persulfate solution, and then the ammonium persulfate solution was added dropwise to the aniline solution, and an in-situ polymerization reaction was carried out under stirring. The in-situ polymerization reaction time was 5 h and the temperature was 0° C. After the in-situ polymerization reaction was completed, the obtained product was filtered to obtain a solid material; then the solid material was washed with deionized water 3 times, and then the solid material was dried in an oven at 60° C. for 8 h to obtain PANI (C1);

[0140] (2) 3 mg of the above PANI was dispersed in 1 mL of pine alcohol and ground into a paste. The paste was applied to the surface of an Al2O3 tube with a length of 4 mm and an inner diameter of 0.8 mm using a brush. The Al2O3 tube had two gold electrodes with a distance of 1 mm between them. Two platinum wires were connected to each gold electrode respectively. After the Ni / Cr wire passed through the Al2O3 tube, it was welded to the substrate together with the platinum wire to obtain an ammonia gas sensor D1.

[0141] Comparative Example 2

[0142] (1) 0.1 g of TiO2 was dispersed in 10 mL of deionized water to obtain a TiO2 solution, 700 μL of aniline was dissolved in 10 mL of 1 mol / L hydrochloric acid solution to obtain an aniline solution, and then the aniline solution was added to the TiO2 solution to obtain an aniline / TiO2 mixture (the solid-liquid ratio of TiO2 to aniline was 1 g:7 mL); the aniline / TiO2 mixture was placed in a 100 mL beaker and ultrasonically treated for 0.5 h (ultrasonic temperature was 25° C., ultrasonic power was 800 W), and then stirred in an ice-water bath at 0° C. for 2 h to obtain an aniline / TiO2 dispersion;

[0143] (2) 1.5 g of ammonium persulfate was dissolved in 10 mL of 1 mol / L hydrochloric acid solution to obtain an ammonium persulfate solution, and then the ammonium persulfate solution was added dropwise to the aniline / TiO2 dispersion, and an in-situ polymerization reaction was carried out under stirring. The in-situ polymerization reaction time was 5 h and the temperature was 0° C. After the in-situ polymerization reaction was completed, the obtained product was filtered to obtain a solid material; then the solid material was washed with deionized water for 3 times, and then the solid material was dried in an oven at 60° C. for 8 h to obtain a PANI-TiO2 composite material C2;

[0144] (3) Take 3 mg of PANI-TiO2 composite material C1 and disperse it in 1 mL of pine alcohol. Grind it into a paste and apply the paste to the surface of an Al2O3 tube with a length of 4 mm and an inner diameter of 0.8 mm using a brush. The Al2O3 tube has two gold electrodes with a distance of 1 mm between the two gold electrodes. Two platinum wires are connected to each gold electrode respectively. After the Ni / Cr wire passes through the Al2O3 tube, it is welded to the substrate together with the platinum wire to obtain an ammonia gas sensor D2.

[0145] Comparative Example 3

[0146] The method of Comparative Example 2 is followed, except that TiO2 is replaced by In2O3, to obtain a PANI-In2O3 composite material C3, and further to obtain an ammonia gas sensor D3.

[0147] Comparative Example 4

[0148] The method of Comparative Example 2 is followed, except that TiO2 is replaced by WO3, to obtain a PANI-WO3 composite material C4, and further to obtain an ammonia gas sensitive sensor D4.

[0149] Test Example 1

[0150] The SEM image of CoMoO4 obtained in Example 1 was detected by scanning electron microscopy. Figure 1 As shown. Figure 1 It can be seen that the surface of CoMoO4 is smooth, the shape of CoMoO4 is rod-like, the diameter of CoMoO4 is 0.5-200 μm, and the length is 5-30 μm.

[0151] Test Example 2

[0152] The SEM image of the PANI-CoMoO4 composite material A1 prepared in Example 1 was detected by scanning electron microscopy. The results are as follows: Figure 2 As shown, according to Figure 2 It can be seen that the surface of CoMoO4 becomes rough, which indicates that after in-situ polymerization, PANI is successfully loaded on the surface of CoMoO4 and a large number of rough particles are formed on the surface of CoMoO4, which provides abundant active sites for ammonia adsorption.

[0153] Test Example 3

[0154] The TEM image of the PANI-CoMoO4 composite material A1 prepared in Example 1 was detected by transmission electron microscopy. The results are as follows: Figure 3 As shown, based on Figure 3 It can be seen that there is an obvious heterogeneous interface between PANI and CoMoO4, which also proves that PANI is uniformly loaded on the surface of CoMoO4 and the PANI-CoMoO4 composite material A1 is successfully prepared.

[0155] Test Example 4

[0156] The XRD curves of PANI used in Example 1, CoMoO4 and PANI-CoMoO4 composite material A1 were detected by X-ray diffractometer and compared with the XRD standard card JCPDS NO.21-0868 of CoMoO4. The results are as follows: Figure 4 As shown, the diffraction peaks of the prepared CoMoO4 all correspond to the XRD standard card of CoMoO4, and there are no extra impurity peaks, indicating that the synthesized CoMoO4 has a high purity, and the diffraction peaks of the PANI-CoMoO4 composite material A1 contain the characteristic peaks of PANI and CoMoO4, indicating that the preparation of the composite material is successful.

[0157] Test Example 5

[0158] Test surface area:

[0159] The specific surface areas of Examples A1-A10 and Comparative Examples C1-C3 were tested using a specific surface area tester (model: F-Sorb 1400CES). The results are shown in Table 1. The specific surface area test result of A1 is shown in Table 1. Figure 5 shown.

[0160] Table 1:

[0161]

[0162] Test Example 6

[0163] Test response strength and response time:

[0164] At room temperature (25°C), B1-B10 and D1-D3 were placed in a mixture of ammonia and air (the concentrations of ammonia were 0.1ppm, 0.5ppm, 1ppm, 4ppm, 15ppm, and 30ppm, respectively) to measure the response intensity (results are shown in Table 2) and response time (results are shown in Table 3). The power-on voltage was 220V. The response intensity and response time of B1 and D1 are shown in Table 3. Figure 6 As shown by Figure 6 It can be seen that the response intensity and response time of B1 prepared in Example 1 to ammonia are significantly better than those of D1 prepared in Comparative Example 1, indicating that the performance of the ammonia gas sensor prepared based on the PANI-CoMoO4 composite material is better than that of the ammonia gas sensor prepared based on the single-component PANI. The ammonia gas sensor B1 prepared from the PANI-CoMoO4 composite material of Example 1 can detect ammonia quickly and with high sensitivity at room temperature, and its resistance curve can be restored to the original value before and after contact with the gas, and the response has good reversibility.

[0165] Table 2:

[0166]

[0167]

[0168] Table 3:

[0169]

[0170] It can be seen from Tables 2 and 3 that the response intensity and response time of B1-B5 are better than those of B6-B10 and D1-D4.

[0171] Test Example 7

[0172] Test selectivity:

[0173] B1 was placed in a mixture of ammonia and air (the concentration of ammonia was 30ppm), a mixture of hydrogen sulfide and air (the concentration of hydrogen sulfide was 30ppm), a mixture of methane and air (the concentration of methane was 30ppm), a mixture of carbon monoxide and air (the concentration of carbon monoxide was 30ppm), and a mixture of nitric oxide and air (the concentration of nitric oxide was 30ppm). The CGS-8 gas sensitive test system was used to measure the response intensity of B1 to ammonia, hydrogen sulfide, methane, carbon monoxide, and nitric oxide. The ratio of the response intensity of B1 to methane, hydrogen sulfide, carbon monoxide and nitric oxide to the response intensity of B1 to ammonia was calculated. The results are as follows: Figure 7 As shown, at the same concentration, the response intensity of hydrogen sulfide is only 0.5% of that of ammonia, the response intensity of methane is only 1.5% of that of ammonia, the response intensity of carbon monoxide is only 1.8% of that of ammonia, and the response intensity of nitric oxide is only 0.9% of that of ammonia. Figure 7 It can be seen that the response intensity of the ammonia gas sensitive sensor prepared by the present invention to ammonia is greater than the response intensity to hydrogen sulfide, methane, carbon monoxide and nitric oxide, indicating that the ammonia gas sensitive sensor prepared by the present invention has excellent selectivity for ammonia detection.

[0174] Test Case 8

[0175] Test repeatability and stability:

[0176] B1 was placed in a mixture of ammonia and air (ammonia concentration was 50 ppm) and the test results after 5 cycles were as follows: Figure 8 As shown, the deviations of the five measurements are all less than 5%, indicating that the sensor has good repeatability and stability.

[0177] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polyaniline-bimetallic oxide composite material, characterized in that: The polyaniline-bimetallic oxide composite material comprises bimetallic oxide and polyaniline loaded on the bimetallic oxide; The specific surface area of ​​the polyaniline-bimetallic oxide composite material is 100-500m 2 / g.

2. The polyaniline-bimetallic oxide composite material according to claim 1, characterized in that: The content of the polyaniline is 200-800 parts by weight relative to 100 parts by weight of the bimetallic oxide.

3. The polyaniline-bimetallic oxide composite material according to claim 1 or 2, characterized in that: The specific surface area of ​​the polyaniline-bimetallic oxide composite material is 150-250 m 2 / g.

4. The polyaniline-bimetallic oxide composite material according to any one of claims 1 to 3, characterized in that: The bimetallic oxide is selected from one or more of CoMoO4, NiCo2O4, ZnCo2O4 or CuCo2O4.

5. A method for preparing the polyaniline-bimetallic oxide composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a bimetallic oxide with aniline to obtain an aniline / bimetallic oxide dispersion; (2) mixing the aniline / bimetallic oxide dispersion obtained in step (1) with an initiator to carry out a polymerization reaction.

6. The preparation method according to claim 5, characterized in that: The specific steps of step (1) include: (a) mixing a bimetallic oxide with water to obtain a bimetallic oxide solution; (b) mixing aniline with a solvent to obtain an aniline solution; (c) mixing the bimetallic oxide solution obtained in step (a) with the aniline solution obtained in step (b), and then performing ultrasound to obtain an aniline / bimetallic oxide mixture; (d) stirring the aniline / bimetallic oxide mixture obtained in step (c) to obtain an aniline / bimetallic oxide dispersion.

7. The preparation method according to claim 6, characterized in that: In step (c), the ultrasonic conditions include: time of 0.5-2h, temperature of 10-40°C, and power of 100-1000W.

8. The preparation method according to claim 6, characterized in that: In step (d), the stirring conditions include: temperature of -1 to 1°C and time of 1 to 3 hours.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The solid-to-liquid ratio of the bimetallic oxide and the aniline is 1 g: (2-8) mL; Preferably, the weight ratio of the bimetallic oxide to the initiator is 1:(5-20).

10. The preparation method according to claim 5 or 9, characterized in that: In step (2), the initiator is selected from one or more of ammonium persulfate, ferric chloride, ferric tetrachloride or aluminum chloride.

11. The preparation method according to any one of claims 5 to 10, characterized in that: In step (2), the polymerization reaction is an in-situ polymerization reaction.

12. The preparation method according to claim 11, characterized in that: In step (2), the conditions of the in-situ polymerization reaction include: time of 5-12 hours and temperature of 0-40°C.

13. Use of the polyaniline-bimetallic oxide composite material according to any one of claims 1 to 4 in ammonia detection.

14. Use of the polyaniline-bimetallic oxide composite material according to any one of claims 1 to 4 in the preparation of an ammonia gas sensor.

15. An ammonia gas sensor, characterized in that: The ammonia gas sensor comprises the polyaniline-bimetallic oxide composite material according to any one of claims 1 to 4.